Treatment Outcomes After Open Reduction, Varus Derotational Osteotomy and Dega Acetabuloplasty in Children With Dislocated Dysplastic Hip: Retrospective Analysis - Raycho I. Kehayov; Anton A. Semenistyy; Pavel R. Georgiev; Aleksander I. Gerchev (Travmatologiâ i Ortopediâ Rossii, 2023)
Background. Treatment of developmental dysplasia of the hip (DDH) poses a great challenge for pediatric orthopedists due to the high risk of complications, the most severe of which are avascular necrosis of the femoral head and recurrent dislocation. In the most severe form of dysplasia, hip dislocation, the surgery is indicated after 18 months of age. However, the issue of determining the exact surgical intervention remains controversial.